Soil corrosivity condition index for buried steel pipeline - Mohamad Nazim, Fatimah Aqilah (2014)
External corrosion is common threat on underground pipeline structures resulting bad impact on human, environment and financial. Researches show that the identification of soil corrosivity level may be determined by the location conditions and suitability of pipeline structures installation. Currently, there is no guideline to assess the condition of site corrosivity by rank or index system for soil conditions in Malaysia. The index system, referring to site corrosivity may provide an early indication on the potential structural damages subjected by soil corrosion prior to pipeline installation and to assess the possible failures of damaged pipeline. This research focuses on the development of soil corrosivity condition index based on soil parameters and site characteristics evaluation for pipeline structure installation and maintenance work purposes. A total of 207 carbon steel coupons originated from X- 70 metal type were installed in site A, B, C, D and E located at peninsular Malaysia for a period of 18 months. The buried coupons were retrieved every 3-months to monitor the corrosion rate by metal loss product coupled with measurement of the soil parameters including Soil Resistivity (Res), Moisture content (Mc), pH, Sulphide (SO4), Sulphate (SO3), Chloride (Cl) and site characteristics information including Soil Type (ST), Water Access (WA) and Disturbance Factor (DF). The results of corrosion rates and soil parameters were analyzed by using statistical method through normality, hypothesis and outlier’s detection test, and the corrosion rates were classified into three categories: crmax, cravg and crmed. The site corrosivity conditions were designed by the classification of four corrosivity percentage levels with 0% as the worst condition and 100% as the best condition namely as “not corrosive” for 76-100%, “mildly corrosive” for 51-75%, “corrosive” for 26-50% and “very corrosive” for 0-25%. A number of six (6) soil parameters and three (3) site characteristic indexes were designed within 0-10, where 0 represent the worst condition and 10 points represent the best condition. The equation model of site corrosivity condition percentage was finally designed along with the weighing factor considerations. The collected data of soil parameters and site characteristics were applied into the model equation to compare the accuracy of designed indices with the existing corrosion rate data. Based on the comparison, the results show that the soil corrosivity condition index proposed model is identical to crmax data and approximately similar to cravg and crmed data for every site. The results also show that site B and C are identified as the most corrosive sites compared to site A, D and E. In conclusion, the proposed index system can assist pipeline operators in selecting the most suitable sites for pipeline installation by considering the level of soil corrosivity, hence, minimising the unnecessary corrosion protection on buried pipeline.